MODULATION OF CYCLIC ADENOSINE MONOPHOSPHATE FOR POTENTIATION OF LONG-ACTING β2-AGONIST AND GLUCOCORTICOIDS IN HUMAN AIRWAY EPITHELIAL CELLS - Kim, Yechan (My University, 2019)
In Canada, asthma is the third most common chronic disease resulting in 250 premature deaths annually and related healthcare expenses exceeding $2.1 billion/year. It is estimated that around 50-80% of asthma exacerbations are due to viral infections. Despite an advanced understanding on how to treat and manage the symptoms of asthma, current therapy is sub-optimal in 35-50% of moderate-severe asthmatics around the world resulting in lung inflammation, persistent impairment of lung function, and increased risk of mortality. Combination of long-acting β2 agonists (LABA) for bronchodilation and glucocorticoids (GCS) to control lung inflammation represent the dominant strategy for the management of asthma. Increasing intracellular cyclic adenosine monophosphate (cAMP) beyond existing combination LABA/GCS are likely to be beneficial for the management of difficult to control asthmatics that are hypo-responsive to mainstay therapy. In human airway epithelial cells (HAEC), cAMP is either exported by transporters or broken down by enzymes, such as phosphodiesterase 4 (PDE4). We have demonstrated that HAEC express ATP Binding Cassette Transporter C4 (ABCC4), an extracellular cAMP transporter. We also show that ABCC4 and PDE4 inhibition can potentiate LABA/GCS anti-inflammatory responses in a human epithelial cell line in a cAMP-dependent mechanism validating the pursuit of novel ABCC4 inhibitors as a cAMP elevating agent for asthma.
McMaster University MASTER OF SCIENCE (2019) Hamilton, Ontario (Medical Sciences) TITLE: Modulation of cyclic adenosine monophosphate for potentiation of long-acting β2-agonist and glucocorticoids in human airway epithelial cells AUTHOR: Yechan Kim, B.HSc. (McMaster University) SUPERVISOR: Dr. Jeremy Alexander Hirota NUMBER OF PAGES: xiv, 81
Keywords: Respiratory; Immunology; ATP Binding Cassette Transporter C4; Phosphodiesterase 4; cAMP; Long acting beta agonist; glucocorticoid; asthma